2012
DOI: 10.1007/978-3-642-35623-0_12
|View full text |Cite
|
Sign up to set email alerts
|

EnglishMash: Usability Design for a Natural Mashup Composition Environment

Abstract: Abstract. The design of mashup tools combines elements from enduser development and software composition in the context of the Web. The challenge for mashup tool designers is to provide end-users with suitable abstractions, programming models and tool support for easily composing mashups out of existing Web services and Web data sources. In this paper we describe the design of a natural mashup composition environment based on the EnglishMash controlled natural language. The environment proactively supports use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These symposiums, together with other international congresses, have promoted several lines of EUD-related investigation akin to the research reported in this paper: (1) attempts at simple programming languages or environments focused on a particular domain, such as EnglishMash (an end user-oriented language with massive natural language use and proactive aids such as autocompleting code) designedbyAghaee and Pautasso [27],orResEval (an EUD environment for mixing R&D domain data sources using a XML-based visual language, which requires knowledge of mark-up languages) created by Muhammad et al [28]; (2) demonstration of the potential of wizard-supported services integration in the EUD field [29,30]; (3) research into human-computer interaction and its particularities in the EUD field, such as [31] stressing how important it is to have user-oriented building blocks in order to focus on solution design rather than the interaction with programming components, or Grudin [32] reporting a study suggesting that HCI consistency is not relevant in the EUD field and can be counterproductive because it hems in user creativity.…”
Section: Related Work: Existing Solutions For End-user Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…These symposiums, together with other international congresses, have promoted several lines of EUD-related investigation akin to the research reported in this paper: (1) attempts at simple programming languages or environments focused on a particular domain, such as EnglishMash (an end user-oriented language with massive natural language use and proactive aids such as autocompleting code) designedbyAghaee and Pautasso [27],orResEval (an EUD environment for mixing R&D domain data sources using a XML-based visual language, which requires knowledge of mark-up languages) created by Muhammad et al [28]; (2) demonstration of the potential of wizard-supported services integration in the EUD field [29,30]; (3) research into human-computer interaction and its particularities in the EUD field, such as [31] stressing how important it is to have user-oriented building blocks in order to focus on solution design rather than the interaction with programming components, or Grudin [32] reporting a study suggesting that HCI consistency is not relevant in the EUD field and can be counterproductive because it hems in user creativity.…”
Section: Related Work: Existing Solutions For End-user Developmentmentioning
confidence: 97%
“…EzWeb, and the proposed model falls into this category. However, other researchers, like [27], [28], etc., take the opposite tack, claiming that, as EUPs are indisputable experts in their domain, it is best practice to design domain-specific EUD tools that will improve the efficiency and ease with which EUPs can build ad hoc solutions to their problems. According to the results of our research, the ideal thing would be a trade-off between the two lines of thought: domain-specific EUD tools can be used to successfully solve simple problems involving components and elements specific to only one or a very well-defined problem domain, whereas a component model like we propose, which is generic and powerful enough to model components for different problem domains (for example, personal organization elements such as email and calendars, heterogeneous visual web resources, RSS data feeds, remote web service invocations, etc.…”
Section: The Domain Specificity Dilemmamentioning
confidence: 99%
“…The evaluation of [11] is a good complement with our study and opens perspectives for future directions. Additionally, usability studies for mashups have been done for e.g., the mashup composition environment [1]. [16] evaluated the usability of mashup applications and [5] discussed metrics to measure usability of mashups.…”
Section: Related Workmentioning
confidence: 99%
“…The "control" consists in the selection of the supported vocabulary and grammar. For example, CoScripter [Leshed et al 2008] allows the user to describe Web-based processes using instructions such as "go to," Aghaee and Pautasso [2012] propose EnglishMash for mashup development with live preview, and Cremene et al [2009] propose a language based on templates.…”
Section: Textualmentioning
confidence: 99%